Genomic insights into Kocuria: taxonomic revision and identification of five IAA-producing extremophiles - Li, Cong-Jian; Jiang, Zhu-Ming; Zhi, Xiao-Yang; Chen, Hua-Hong; Yu, Li-Yan; Li, Guang-Fu; Zhang, Yu-Qin (Frontiers in Microbiology, 2025)
Desert ecosystems have increasingly piqued the interest of microbiologists seeking novel bioactive compounds, as they are viewed as a largely uncharted reservoir of extremophiles with remarkable resilience to severe conditions. The genus Kocuria, belonging to the phylum Actinomycetota, is particularly notable for its documented capacity to flourish in such extreme environmental conditions. In this study, a total of 21 Kocuria strains were isolated from various ecosystems. Using polyphasic taxonomy approaches, eight strains from desert soils (CPCC 205273T, CPCC 205300, CPCC 205290, CPCC 205236T, CPCC 205293, CPCC 205292T, CPCC 205315T, CPCC 205268T) were identified representing five new species of the genus Kocuria. Strains CPCC 205281 and CPCC 205293 were identified as siblings of strain CPCC 205236T, while strains CPCC 205290 and CPCC 205300 were identified as siblings of strain CPCC 205273T. Additionally, K. polaris and K. indcia were determined to be the later heterotypic synonym of K. rosea and K. marina, respectively. Genomic analysis and physiological assays demonstrated that these previously uncharacterized strains were tolerant to high-level salt concentration and UV radiation, key survival traits in desert environments. The fermentation analysis revealed that most strains produced high-level contents of indole-3-acetic acid (IAA), although the complete gene sets for IAA biosynthesis were found in only one strain. Comparative genome analysis further showed that genes related to carbohydrate metabolism and transports were significantly enriched in desert-derived Kocuria strains, indicating adaptation to desert habitats. Collectively, our findings enhance our understanding of Kocuria taxonomy and highlight their genetic adaptation strategies to extreme environments, with potential biotechnological applications.